The „limited recognition” problem and the international presence of the Republic of Kosovo - Szeląg, Paulina (Balcanica Posnaniensia. Acta et studia, 2024)
This paper aims to examine the connection between foreign policy of the states with limited recognition and their security. Author analyzes the position of Kosovo in international relations. Explaines differences between de facto states, quasi-states, unrecognized states, pseudo states and states with limited recognition, arguing that Kosovo should be consider as the latter. Author also points out consequences of international recognition (including the case of Kosovo), shows the main goals of foreign policy of this state and relations between Kosovo and international governmental organizations, which conduct ‘engagement without recognition policy’ and selected countries, which recognized Kosovo as a sovereign state. The paper is based on examination of primary and secondary sources, critical analysis of sources and data analysis. Author argues that limited recognition of Kosovo has a direct influence on foreign policy of this state. This foreign policy is strictly connected with security issues. However, limited recognition reduced foreign policy of Kosovo and made that this country cannot be a party of military pacts, which is crucial in maintaining peace and security in this country.